Determination of scandium in acid mine drainage by ICP-OES with flow injection on-line preconcentration using oxidized multiwalled carbon nanotubes - Jerez, Javier (2014)
An on-line scandium preconcentration and determination system implemented with inductively coupled plasma optical emission spectrometry associated with ﬂow injection was studied. Trace amounts of scandium were preconcentrated by sorption on a minicolumn packed with oxidized multiwalled carbon nanotubes, at pH 1.5. The retained analyte was removed from the minicolumn with 30% (v/v) nitric acid. A total enrichment factor of 225-fold was obtained within a preconcentration time of 300 s (for a 25 mL sample volume). The overall time required for preconcentration and elution of 25 mL of sample was about 6 min; the throughput was about 10 samples per hour. The value of the detection limit was 4 ng L1 and the precision for 10 replicate determinations at 100 ng L1 Sc level was 5% relative standard deviation, calculated from the peak heights obtained. The calibration graph using the preconcentration system was linear with a correlation coefﬁcient of 0.9996 at levels near the detection limits up to at least 10 mg L1 . After optimization, the method was successfully applied to the determination of Sc in an acid drainage from an abandoned mine located in the province of San Luis, Argentina